Integrative Counselling Skills in Action - Culley Sue (Sage Publications, 1993)
This book provides a clear and concise guide to the purposeful use of counselling skills. It has written for counsellors, counsellors in training and professional helpers, whatever their theoretical orientation. Preface, Acknowledgements, Overview: Introducing the Integrative Skills Model, The Beginning Stage: Exploration and Contracting and Assessment, The Foundation Skills of Counselling, The Middle Stage: Action and Closure, Case Study, Index.